Unjuk Kerja Evaporator Pada Mesin Pendingin Dengan Siklus Adsorpsi Menggunakan Energi Surya - Amusadar, Amusadar; Hasbi, Muhammad; Samhuddin, Samhuddin (ENTHALPY, 2021)
Energy  needs  in  Indonesia  continue  to  increase  every  year.  The  largest  use  of energy  is  in  the  industrial  sector,  where  its  needs  reach  42.12%  of  the  total national energy needs. To save energy, energy saving measures are needed in the industrial sector so that the increase in energy demand can be restrained. So we conducted  research  on  the  performance  of  the  evaporator  in  a  refrigeration machine  with  an  adsorption  cycle  using  solar  energy.  The  purpose  of  this  study was  to  determine  the  working  process  of  the  evaporator  with  activated  carbon refrigeration  and  to  determine  the  efficiency  of  the  evaporator  in  the  activated carbon  pair  adsorption  refrigeration  system.  This  research  was  conducted  by observing and recording the evaporator temperature of the refrigeration machine every hour. The results of the research in three days of testing, namely, on the first day the highest evaporator temperature increase was at 16.00 o'clock, which was 33.2 oC and the lowest evaporator temperature was at 07.00 o'clock, which was 25.1 oC. On the second day, the highest increase in evaporator temperature was at 16.00,  which  was  32.2  oC  and  the  lowest  evaporator  temperature  was  at  07.00, which  was  23.8  oC.  On  the  third  day,  the  highest  increase  in  evaporator temperature was at 36.4 oC and the lowest evaporator temperature was at 06.00, which was 24.5 oC. Kata kunci: Adsorption, evaporator, temperature